The unbeatable Squirrel Girl. - North, Ryan 1980- (Marvel now!, 2015)
"Squirrel Girl meets potential new allies, including Chipmunk Hunk, Koi Boi and...Girl Squirrel?! Yes! But the two rodent-themed heroines don't quite see eye-to-beady-eye-- and Squirrel Girl's dislike might be justified! Now, as the world goes mad and the Avengers attack, Squirrel Girl must face Ratatoskr, the Norse god of squirrels! There's a theme in this book, I don't know if you can tell. The fate of the world hangs in the balance, though, we promise. Featuring fights! Feelings! Sass! Punches! Friendship! A character named Hippo who is literally a hippo! And several tails (tales) of Squirrel Girl from all kinds of perspectives!"--Unedited summary from book.